The Impact of Rice Production, Consumption and Importation in Nigeria: The Political Economy Perspectives - Terungwa, Terwase Isaac; Yuguda, Madu Abdulrazak (International Journal of Sustainable Development & World Policy, 2014)
Nigeria’s population is estimated at 174, 507,539 with the annual growth rate of 2.54%. The country is endowed with enormous mineral and natural resources with vast land adjudged to be the most fertile and suitable for agriculture. Rice demand and consumption is high among its people irrespective of their region or culture. This paper attempts to investigate the level of the country’s production, consumption and importation of rice, with a view to establishing its impact on its economy and development. The methods adopted for obtaining data for the study were purely empirical and secondary. It was found amongst others that; while the level of production of rice is low, the consumption is high and its importation is highly inelastic. It was recommended that, deliberate attempts must be made by government in terms of policy to improve its agricultural base particularly in rice production not only as a substitute for its importation and domestic use, but export as well. This will go a long way in increasing foreign earnings, which can be replicated, and serve to complement the country’s economic growth and development.